Optimization of the key parameters in the carrot seed guiding system using DEM-CFD analysis - Sun, Yue; Zhang, Lianglong; Yang, Fan; Wang, Fangyan; Jiang, Jingtao (International Journal of Agricultural and Biological Engineering, 2025)
The objective of this research was to enhance the stability and consistency of seed distribution during carrot planting. The impact of the seed guide tube’s structure on seeding quality was examined, leading to the design of a cycloidal seed guide system augmented by positive pressure airflow. By conducting kinematic modeling of the collision position of the seeds within the seed guiding system, as well as considering the seed guiding process and the seed drop position, the significant parameters influencing the final velocity of the seeds were determined. Employing a coupled Discrete Element Method-Computational Fluid Dynamics (DEM-CFD) simulation, the effects of different structural and operating parameters of the seed guide tube on the seed trajectory and airflow field were analyzed. A three-factor five-level orthogonal test was then utilized to examine the influence of each factor on each index, with the optimal conditions identified as an inlet airflow velocity of 0.077 m/s, a 45° tilt angle for the airflow branch tube, and a seed initial velocity of 0.1 m/s. Under these parameters, the qualification index was recorded as 94.1%, with a coefficient of variation of 3.2%. Bench testing conducted under the same conditions showed a decrease of 0.07% in the qualification index, and an increase of 1.875% in the coefficient of variation, with errors relative to the simulation results within acceptable bounds. These findings enhance the stability and reliability of the seed guiding system during carrot sowing operations, aligning with the demands of precision sowing. Key words: carrot; seed guiding process; seed motion analysis; air assisted; DEM-CFDDOI: 10.25165/j.ijabe.20251806.9763Citation: Sun Y, Zhang L L, Yang F, Wang F Y, Jiang J T. Optimization of the key parameters in the carrot seed guiding system using DEM-CFD analysis. Int J Agric & Biol Eng, 2025; 18(6): 112–121.